Studies on Homalomeneae (Araceae) of Sumatera VI: Two remarkable new species of Homalomena [Chamaecladon Clade] - Wong, Sin Yeng; Boyce, Peter C.; Hay, Alistair (Firenze University Press, 2020)
Two ornamental new species of Sumateran Homalomena [Chamaecladon] are described: Homalomena anthurioides S.Y.Wong, P.C.Boyce & A.Hay and H. pexa S.Y.Wong, P.C.Boyce & A.Hay. These novelties represent a continuation of discoveries on Sumatera of species with uniquely, for Asia, highly elaborated epidermis.